Batman : killing time - King, Tom, 1978-; Kane, Bob; Finger, Bill, 1914-1974 (DC Comics, 2022)
"Catwoman, The Riddler, and The Penguin join forces to pull off the greatest robbery in the history of Gotham City. And their prize? A mysterious and priceless artifact in the secret possession of Bruce Wayne! But, as the events unfold, what fun is a heist without a bloody double cross or two? The blockbuster team of Tom King and David Marquez bring on epic, white-knuckled, action-packed tale of a young Batman desperate to recover his most prized possession from a host of violent rogues before the clock strikes The Killing Time..."--Back cover.